Phenological growth stages in chia (Salvia hispanica L.) according to the BBCH scale - Perez Brandan, Jimena (2019)
Chia is a sub-tropical crop which recently reinforced its commercial value due to the high proportion of omega-3 in their grains. Although the growing demand for this crop, there is not a standardized scale to be used as a criterion to quantify their phenology. The aim of this study was to apply the Biologische Bundesanstalt, Bundessortenamt and Chemical Industry (BBCH) system to chia in order to develop a phenological scale which quantify the phenology of this underutilized crop. Eight principal growth stages were described: germination (0), leaf appearance (1), shoot appearance (2), verticillaster growth (5), flowering (6), fruit changes (7), ripening (8), and senescence (9). Critical crop stages which should be considered for management practices are cotyledons emerged through soil surface (09) and full flowering (65). In the first, timely crop operations could implicate a good stand of plants, whereas in the latter a high grain set. Growers, researchers, and breeders aimed to introduce this crop into new areas of cultivation could benefit from using the scale developed here in order to match critical growth stages of this crop with favorable environmental conditions.